Elaboração de um compósito a partir de resíduos da cultura de girassol com propriedades de absorção sonora - Carvalho, Patrícia Stefan de (2019)
This research had the objective to develop a composite with acoustic properties from the residues of the sunflower culture. The work follows cleaner production practices in conjunction with sustainable innovation. The cleaner production is present in the recycling of waste, and provides environmental and economic benefits. The innovation is sustainable because it considers the study of a new material that aims at the use of renewable and vegetal raw material: the stalk of sunflower, residue of the culture after the harvest. The composite was the result of mixing sunflower stalk, gypsum and water as a binder, and sodium benzoate as a fungus proliferation inhibitor. Composites of different particle size of stalks were subjected to an impedance tube test. Through the ANOVA test and Duncan test, their performance was compared at a significance level of 5%, indicating the best average sound absorption performance of 0,8293 in the 1,18 mm particle composite at 2,36 mm. The flexural strength test showed a value of 0,69 MPa, being classified as reasonably good considering the fact that the material did not have a structural end and compared it with other composites developed in researches. The manufacturing cost of the composite was 76,09% lower than that of a commercial material and economically attractive. The environmental assessment was positive, considering that it met the requirements of cleaner production and sustainable innovation, since there was the use of recyclable raw material of low cost and low impact to the environment.